Luminescent rare earth element doped LaOCl flaky crystal material as well as preparation method and application thereof
By combining heat treatment and KCl flux, LaOCl plate-like crystal materials with domain sizes greater than 100 μm were prepared, solving the problems of small domain size and disordered growth in the prior art, improving luminescence purity and compatibility with micro-nano fabrication, and expanding the application range.
Patent Information
- Application Number
- CN202511256127.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-04
- Publication Date
- 2025-12-12
AI Technical Summary
In the existing technology, LaOCl plate-like crystal materials doped with rare earth elements have problems such as small crystal domain size and disordered growth and arrangement, resulting in low luminescence purity and limiting their application in the field of light-emitting devices.
Using anhydrous LaCl3, anhydrous NH4Cl, anhydrous KCl, and anhydrous LnCl3 as raw materials, LaOCl plate-like crystal materials with domain sizes of not less than 100 μm were prepared by adjusting the conditions on the growth substrate through heat treatment. KCl was used as a flux to induce the ordered growth and arrangement of the wafers, simplifying the operation process.
The orderly growth and arrangement of LaOCl sheet-like crystal materials were achieved, which improved the luminescence purity and the integration compatibility of micro-nano fabrication, and broadened its application scope in the field of micro-nano optoelectronic devices.
Smart Images

Figure CN121108994A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of light-emitting device technology, and relates to a light-emitting rare earth element-doped LaOCl sheet-like crystal material, and more particularly to a light-emitting rare earth element-doped LaOCl sheet-like crystal material, its preparation method and application. Background Technology
[0002] Lanthanum oxychloride (LaOCl), as a typical rare-earth layered halide oxide, has the characteristics of ultrawide bandgap, low defect density, high quantum efficiency and good integration compatibility. In addition, its bandgap is in the range of 4.8 eV to 5.5 eV, and the corresponding cutoff wavelength is in the solar-blind band (200 nm to 280 nm). Therefore, LaOCl materials have natural spectral selectivity for solar-blind ultraviolet light and show good application prospects in the field of photoelectric detection.
[0003] LaOCl is also an excellent substrate material for fabricating light-emitting devices: the thickness of its layered structure can be precisely controlled down to a single atomic layer, exhibiting a significant quantum confinement effect and promising the potential for direct bandgap luminescence; simultaneously, LaOCl material inherently possesses rare-earth ion lattice sites, namely Tb 3+ Eu 3+ Ce 3+ The successful doping of luminescent rare earth ions has provided favorable conditions. These rare earth ions, due to their unique 4f electron transition, possess both high color purity and strong chemical stability, and have been widely used in the lighting and display fields.
[0004] Therefore, doping with luminescent rare earth elements can not only modulate the physical properties of LaOCl materials, such as the band gap, but also broaden their application range in the field of light-emitting devices. For example, in the LED era, rare earth-doped fluorescent materials coupled with semiconductor chips have become a key component in realizing high-performance white LEDs. At the same time, rare earth luminescent materials have also shown broad application prospects in new lighting fields such as laser lighting, OLEDs, backlights, and special light sources such as UV or NIR, and the compatibility of LaOCl materials with rare earth ions provides a stable guarantee for these applications.
[0005] However, the LaOCl nanosheets prepared by doping LaOCl with luminescent rare earth elements in the existing technology have the problem of small crystal domain size, i.e. disordered growth and arrangement of the wafers, which greatly limits their application in the field of light-emitting devices.
[0006] For example, CN110358539A discloses a micro / nano structure LaOCl:Eu 3+ The method for preparing luminescent materials involves using La₂O₃ and Eu₂O₃ as raw materials, dissolving them in nitric acid, using ammonia as a precipitant, and preparing La(OH)₃:Eu₂O₃ through co-precipitation. 3+Precursor powder; the precursor powder was mixed with KCl and LiCl, heated and maintained at that temperature in a reactor, then removed and cooled, washed, filtered, and dried to obtain the micro / nano structured LaOCl:Eu. 3+ Luminescent materials. However, this micro / nano structure LaOCl:Eu 3+ The luminescent material has a low domain size.
[0007] For example, RO132582B1 discloses a method for preparing a LaOCl luminescent material doped with rare earth elements Ce, Tb, and Eu. According to this invention, the method involves a sol-gel reaction of lanthanum acetate with europium acetate, cerium, and terbium in a mixture of trichloroacetic acid and water in an ethanol and isopropanol solution at a molar ratio of 1:0.75:0.2:0.8. The resulting transparent sol is then mixed at ambient temperature for 2 hours until the liquid sol evaporates, and then dried at 60°C for 24 hours. The dried gel is then calcined as a powder at 500°C for 1 hour to form a LaOCl crystal matrix doped with cerium, erbium, and europium, exhibiting X-ray luminescence. However, this LaOCl crystal matrix doped with cerium, erbium, and europium has a low domain size and low luminescence purity.
[0008] In summary, the existing rare-earth element-doped LaOCl sheet crystal materials have the following defects: small crystal domain size, i.e. disordered growth and arrangement of the wafers, and low luminescence purity. These defects greatly limit the integration compatibility of LaOCl sheet crystal materials with micro and nano fabrication, and thus seriously hinder the further expansion of the application range of LaOCl sheet crystal materials. Summary of the Invention
[0009] To address the shortcomings of existing technologies, the present invention aims to provide a luminescent rare-earth element-doped LaOCl sheet-like crystal material, its preparation method, and its applications. The domain size of the LaOCl sheet-like crystal material is not less than 100 μm. The domain size of the LaOCl sheet-like crystal material is not less than 100 μm, indicating that the wafers are grown and arranged in an ordered manner. Therefore, the LaOCl sheet-like crystal material has good integration compatibility with micro-nano fabrication. Furthermore, the ordered arrangement structure of the LaOCl sheet-like crystal material effectively improves the efficiency and convenience of nanosheet transfer and stacking processes, providing a reliable foundation for heterogeneous integration of materials and micro-nano devices. In addition, the LaOCl sheet-like crystal material also has high luminescence purity. Therefore, the LaOCl sheet-like crystal material has a wider range of applications in the field of micro-nano optoelectronic devices.
[0010] To achieve this objective, the present invention adopts the following technical solution:
[0011] In a first aspect, the present invention provides a LaOCl sheet-like crystal material doped with luminescent rare earth elements, wherein the luminescent rare earth elements in the LaOCl sheet-like crystal material include any one or a combination of at least two of Tb, Eu, or Ce;
[0012] The domain size of the LaOCl plate-like crystal material is not less than 100 μm.
[0013] In this invention, the luminescent rare earth element in the LaOCl plate-like crystal material includes any one or a combination of at least two of Tb, Eu, or Ce. Typical but non-limiting combinations include combinations of Tb and Eu, Eu and Ce, Tb and Ce, or combinations of Tb, Eu, and Ce, preferably Tb and / or Eu.
[0014] In this invention, the domain size of LaOCl sheet-like crystal material refers to the size of a single continuous crystal region (i.e., "domain", which refers to a continuous region with ordered internal structure and periodic atomic arrangement) in LaOCl nanosheets; a larger domain size means fewer grain boundaries inside the material and a higher degree of order in atomic arrangement.
[0015] In this invention, the domain size of the LaOCl plate-like crystal material is not less than 100 μm, and can be, for example, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1 mm, 2 mm, 3 mm, 4 mm or 5 mm, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0016] The LaOCl plate-like crystal material provided by this invention has a domain size of not less than 100 μm, indicating that the wafers are grown and arranged in an orderly manner. Therefore, the LaOCl plate-like crystal material has good integration compatibility with micro-nano processing and has a wider range of applications.
[0017] The LaOCl sheet-like crystal material provided in this invention has an ordered arrangement structure, which can effectively improve the efficiency and convenience of nanosheet transfer and stacking processes, providing a reliable foundation for heterogeneous integration of materials and micro / nano devices, and further broadening the application scope of LaOCl sheet-like crystal materials in the field of micro / nano optoelectronic devices.
[0018] The LaOCl plate-like crystal material provided in this invention has fewer emission peaks and a smaller half-width at half-maximum of the main emission rare earth element peaks, thus exhibiting higher emission purity and further broadening the application range of the LaOCl plate-like crystal material.
[0019] Preferably, the percentage of the total molar amount of metal elements in the LaOCl plate-like crystal material is 1.00% to 5.10%, for example, it can be 1.00%, 1.50%, 2.00%, 2.50%, 3.00%, 3.50%, 4.00%, 4.50%, 5.00%, or 5.10%, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0020] Preferably, the wafers in the LaOCl sheet-like crystal material are rectangular wafers.
[0021] In a second aspect, the present invention provides a method for preparing the LaOCl plate-like crystal material described in the first aspect, the method comprising:
[0022] A mixture of LaCl3, NH4Cl, KCl and LnCl3 was obtained, and the mixture was heat-treated on a growth substrate to obtain LaOCl plate-like crystal material.
[0023] In the LnCl3, Ln is any one or a combination of at least two of Tb, Eu, or Ce.
[0024] In this invention, Ln in LnCl3 is any one or a combination of at least two of Tb, Eu, or Ce. Typical but non-limiting combinations include combinations of Tb and Eu, Eu and Ce, Tb and Ce, or combinations of Tb, Eu, and Ce, preferably Tb and / or Eu.
[0025] Several methods for preparing LaOCl nanomaterials have been disclosed in the prior art. The first method uses Li + Preparation of LaOCl:Eu by co-doping 3+ Nanocrystals: through Li + With Eu 3+ The first method involves co-doping to obtain agglomerated capsule-like particles with excellent red light emission performance, a broad excitation band, and high thermal stability; the second method uses a solid-state reaction to prepare layered LaOCl:Eu 2+ Phosphor: A layered rectangular sheet with a thickness of 2μm to 4μm is synthesized through a solid-state reaction; this material exhibits blue light emission properties. A third method involves synthesizing LaOCl:Tm using a conventional sol-gel process. 3+ 、LaOCl:Dy 3+ Nanocrystals: Preparation of single-doped Tm via sol-gel method 3+ or Dy 3+ The fourth method involves preparing LaOCl:Tm nanocrystals using the Pechini sol-gel method. 3+ 、LaOCl:Dy3+ and LaOCl:Tm 3+ ,Dy 3+ Nanocrystals: Blue luminescence (Tm) was obtained using the sol-gel process. 3+ Doped), yellow luminescence (Dy) 3+ Doping) and white light emission (Tm) 3+ With Dy 3+ (Co-doped) nanocrystals.
[0026] However, the existing methods for preparing rare earth-doped LaOCl nanomaterials mainly involve solid-state reaction, sol-gel, hydrothermal / solvothermal, and co-precipitation methods. However, these methods are difficult to prepare LaOCl plate-like crystal materials with domain sizes larger than tens of micrometers and thicknesses as small as a single layer, and they cannot achieve the orderly growth and arrangement of the crystal wafers.
[0027] In the preparation method provided by the present invention, by selecting anhydrous LaCl3, anhydrous NH4Cl, anhydrous KCl and anhydrous LnCl3 (Ln is any one or a combination of at least two of Tb, Eu or Ce) as raw materials, and by adjusting the growth conditions of single crystal nanosheets on the growth substrate through heat treatment, the domain size of the LaOCl plate-like crystal material prepared by the preparation method can reach hundreds of micrometers, which is a significant improvement compared with the prior art.
[0028] In the preparation method provided by the present invention, the water content of LaCl3, NH4Cl, KCl and LnCl3 affects the domain size of the final grown LaOCl plate-like crystal material. The LnCl is preferably an Aladdin ultra-dry grade product with a purity higher than 99.9%.
[0029] In the preparation method provided by this invention, the raw materials include KCl. KCl, as a flux, can repeatedly induce the directional splicing of LaOCl wafers, avoiding the problem of random stacking of wafers in traditional methods, and finally achieving the ordered growth and regular arrangement of nanosheets, thereby improving the structural uniformity of the prepared LaOCl sheet crystal material.
[0030] In the preparation method provided by the present invention, the obtained mixture is heat-treated on a growth substrate. The growth substrate provides a flat growth interface for the growth of LaOCl nanosheets. Combined with the synergistic effect of heat treatment and KCl flux, rectangular layered wafers are induced to be neatly arranged on the growth substrate.
[0031] In the preparation method provided by the present invention, the mixture obtained is heat-treated on the growth substrate, which not only promotes the formation of a thermodynamically stable phase, which is beneficial to defect repair, reduces non-radiative recombination centers, and improves luminescence efficiency, but also helps to improve the uniformity of luminescent rare earth element doping, thereby improving the luminescence purity of LaOCl plate crystal material.
[0032] The preparation method provided by this invention involves directly mixing solid raw materials such as LaCl3, NH4Cl, KCl and LnCl3 and then subjecting them to heat treatment. This eliminates the need for complex liquid phase treatment processes, avoids solvent evaporation in the sol-gel method, high-pressure reaction conditions in the hydrothermal method, and multi-step filtration and washing steps in the coprecipitation method. This significantly simplifies the operation process, greatly improves the convenience and operability of the process, and is suitable for large-scale production.
[0033] The preparation method provided by this invention directly mixes solid raw materials such as LaCl3, NH4Cl, KCl and LnCl3 and then performs heat treatment, eliminating the waste liquid treatment step that is inevitably generated in the liquid phase reaction, which is more environmentally friendly.
[0034] Preferably, the mixing method includes grinding, and the grinding time is 10 min to 20 min, for example, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0035] In this invention, the doping amount of luminescent rare earth elements in the LaOCl plate crystal material can be controlled by adjusting the ratio of LaCl3, NH4Cl, KCl and LnCl3 added during grinding.
[0036] Preferably, the grinding is performed in a glove box.
[0037] Preferably, the moisture and oxygen content in the glove box are each independently less than 0.01 ppm, for example, 0.001 ppm, 0.002 ppm, 0.003 ppm, 0.004 ppm, 0.005 ppm, 0.006 ppm, 0.007 ppm, 0.008 ppm, 0.009 ppm or 0.01 ppm, but are not limited to the listed values; other unlisted values within this range also apply.
[0038] In this invention, the grinding is carried out in a glove box, which can prevent moisture from interfering with LaCl3, NH4Cl, KCl and LnCl3.
[0039] Preferably, the grinding process further includes: weighing LaCl3, NH4Cl, KCl and LnCl3 in a glove box and then placing them in a mortar used for grinding.
[0040] Preferably, the molar ratio of LaCl3 to LnCl3 in the mixture is (5 to 40):1, for example, it can be 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1 or 40:1, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0041] Preferably, the molar ratio of NH4Cl to LnCl3 in the mixture is (2 to 20):1, for example, it can be 2:1, 4:1, 6:1, 8:1, 10:1, 12:1, 14:1, 16:1, 18:1 or 20:1, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0042] Preferably, the molar ratio of KCl to LnCl3 in the mixture is (2-16):1, for example, it can be 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1 or 16:1, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0043] Preferably, the mixing and heat treatment process further includes pouring the resulting mixture into a container containing a growth substrate.
[0044] In this invention, the growth substrate is placed in a container, and the growth substrate can be placed horizontally with the bottom of the crucible (i.e., the growth substrate is parallel to the bottom of the crucible) and / or perpendicular to the bottom of the crucible (i.e., the growth substrate is perpendicular to the bottom of the crucible), preferably perpendicular to the bottom of the crucible.
[0045] Preferably, the growth substrate comprises a double-polished c-plane sapphire substrate.
[0046] Preferably, the crystal orientation of the sapphire substrate is... <0001> .
[0047] Preferably, the surface dimensions of the sapphire substrate are 10mm × 10mm.
[0048] Preferably, the container includes a crucible.
[0049] In the preparation method provided by this method, by precisely adjusting the matching degree between the size of the crucible and the amount of materials, a closed space is formed during the reaction process. In addition, KCl is used as a flux to repeatedly induce the directional splicing of LaOCl wafers, which can further promote the orderly growth and regular arrangement of nanosheets, thereby further improving the structural uniformity of the prepared LaOCl plate crystal material.
[0050] Preferably, the growth substrate is further cleaned before pouring.
[0051] Preferably, the cleaning process includes: in an ultrasonic cleaner, the growth substrate is ultrasonically cleaned sequentially with acetone, ethanol, and deionized water, then the growth substrate is removed, rinsed with deionized water, and the surface of the growth substrate is dried with nitrogen gas. Finally, it is transferred to a vacuum chamber in a glove box for storage.
[0052] Preferably, in the ultrasonic cleaner, the growth substrate is ultrasonically cleaned sequentially with acetone, ethanol, and deionized water for 5 to 15 minutes. For example, the time intervals can be 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, or 15 minutes, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0053] Preferably, the heat treatment includes a first heating, a first holding, a second heating and a second holding in sequence, resulting in a growth substrate with LaOCl plate-like crystal material grown on its surface.
[0054] In this invention, residual moisture in the mixture is removed by a first heating and a first heat preservation.
[0055] In this invention, after setting the process parameters for the first heating, the first holding, the second heating, and the second holding of the muffle furnace, the heating power supply is turned on to start growth; by providing a high-temperature environment to the mixture, diffusion and surface contact occur between the materials in the mixture; then, local atomic rearrangement forms crystal nuclei, and a new phase begins to form; finally, the crystal nuclei continue to grow and migrate rapidly under high-temperature conditions, and form a dense microstructure under the induction of flux.
[0056] Preferably, the first heating rate is 10℃ / min to 30℃ / min, for example, it can be 10℃ / min, 12℃ / min, 14℃ / min, 16℃ / min, 18℃ / min, 20℃ / min, 22℃ / min, 24℃ / min, 26℃ / min, 28℃ / min or 30℃ / min, but is not limited to the listed values. Other unlisted values within this range are also applicable, and the endpoint temperature is the temperature of the first heat preservation.
[0057] Preferably, the temperature of the first heat preservation is 250℃~300℃, and the time is 40min~80min.
[0058] In this invention, the temperature of the first heat preservation is 250℃~300℃, for example, it can be 250℃, 255℃, 260℃, 265℃, 270℃, 275℃, 280℃, 285℃, 290℃, 295℃ or 300℃, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0059] In this invention, the first heat preservation time is 40 min to 80 min, for example, it can be 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min or 80 min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0060] Preferably, the second heating rate is 5℃ / min to 15℃ / min, for example, it can be 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min, 11℃ / min, 12℃ / min, 13℃ / min, 14℃ / min or 15℃ / min, but it is not limited to the listed values. Other unlisted values within this range are also applicable, and the endpoint temperature is the temperature of the second heat preservation.
[0061] Preferably, the second heat preservation temperature is 900℃~1100℃, and the time is 20min~40min.
[0062] In this invention, the second heat preservation temperature is 900℃~1100℃, for example, it can be 900℃, 920℃, 940℃, 960℃, 980℃, 1000℃, 1020℃, 1040℃, 1060℃, 1080℃ or 1100℃, but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0063] In this invention, the second heat preservation time is 20 min to 40 min, for example, it can be 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min or 40 min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0064] In the preparation method provided by this invention, the second heat preservation is carried out at a high temperature. The high temperature environment promotes the full diffusion of reactants and lattice recombination, promotes the formation of thermodynamically stable phases, effectively reduces impurity phases and defects, and significantly improves the phase purity and crystal quality of LaOCl plate crystal materials.
[0065] Preferably, the heat treatment is followed by a first cooling and a second cooling in sequence.
[0066] Preferably, the first cooling rate is 1℃ / min to 10℃ / min, and the final temperature is 600℃ to 800℃.
[0067] In this invention, the first cooling rate is 1℃ / min to 10℃ / min, for example, it can be 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min or 10℃ / min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0068] In this invention, the endpoint temperature of the first cooling is 600℃ to 800℃, for example, it can be 600℃, 620℃, 640℃, 660℃, 680℃, 700℃, 720℃, 740℃, 760℃, 780℃ or 800℃, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0069] Preferably, the second cooling rate is 40℃ / min to 100℃ / min, and the final temperature is 10℃ to 35℃.
[0070] In this invention, the second cooling rate is 40℃ / min to 100℃ / min, for example, it can be 40℃ / min, 50℃ / min, 60℃ / min, 70℃ / min, 80℃ / min, 90℃ / min or 100℃ / min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0071] In this invention, the endpoint temperature of the second cooling is 10℃ to 35℃, for example, it can be 10℃, 12℃, 14℃, 16℃, 18℃, 20℃, 22℃, 24℃, 26℃, 28℃, 30℃, 32℃, 34℃ or 35℃, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0072] Preferably, the heat treatment further includes: sequentially cleaning and transferring the growth substrate on which LaOCl plate-like crystal material is grown on the surface.
[0073] Preferably, the cleaning method includes immersing the growth substrate with LaOCl plate-like crystal material on its surface in deionized water three times, each time for 3 to 10 minutes, to obtain a cleaned growth substrate with LaOCl plate-like crystal material on its surface.
[0074] In this invention, during the cleaning process, each soaking lasts from 3 to 10 minutes, for example, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, or 10 minutes, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0075] Preferably, the substrate transfer method includes: inverting a PDMS stamp on a cleaned growth substrate on which LaOCl plate-like crystal material has been grown, and then immersing it in a mixture of ethanol and water to obtain a PDMS stamp with nanosheets attached; then, attaching the PDMS stamp with nanosheets attached to a target substrate, and then heating the target substrate to cause the nanosheets to detach from the PDMS stamp, thereby transferring the growth material to the target substrate and obtaining LaOCl plate-like crystal material.
[0076] In this invention, the PDMS stamp is a flexible stamp made of polydimethylsiloxane, which is widely used in micro-nano processing, biochips, flexible electronics and other fields, and plays a core role in soft lithography technology.
[0077] In this invention, the PDMS stamp is formed by curing a mixture of PDMS prepolymer and curing agent in a customized PDMS mold with micropillars. The cross-section of the micropillars is a square with a side length of 30μm to 50μm and a height of 30μm to 50μm. The spacing between the micropillars in the PDMS mold is 15μm to 25μm.
[0078] In this invention, the cross-section of the micropillar is a square with a side length of 30μm to 50μm. For example, it can be 30μm, 32μm, 34μm, 36μm, 38μm, 40μm, 42μm, 44μm, 46μm, 48μm or 50μm, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0079] In this invention, the height of the microcolumn is 30μm to 50μm, for example, it can be 30μm, 32μm, 34μm, 36μm, 38μm, 40μm, 42μm, 44μm, 46μm, 48μm or 50μm, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0080] In this invention, the micropillar spacing in the PDMS mold is 15μm to 25μm, for example, it can be 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm or 25μm, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0081] In this invention, immersion in a mixture of ethanol and water can promote the separation between the nanosheets and the growth substrate, thereby achieving the peeling of the growth material from the growth substrate.
[0082] In this invention, the volume ratio of ethanol to water in the ethanol-water mixture is (0.5 to 1.5):1, for example, it can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0083] Preferably, the target substrate comprises a single-sided polished silicon substrate with a crystal orientation of (100).
[0084] Preferably, one side surface of the target substrate has a size of 10mm × 10mm.
[0085] Preferably, during the substrate transfer, the temperature at which the target substrate is heated is 40°C to 70°C, for example, 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, or 70°C, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0086] As a preferred embodiment of the preparation method of the present invention, the preparation method includes:
[0087] (1) In an ultrasonic cleaner, acetone, ethanol, and deionized water are sequentially applied to the crystal orientation. <0001> After ultrasonic cleaning of the sapphire substrate for 5 to 15 minutes, the sapphire substrate is removed, rinsed with deionized water, and then the surface of the sapphire substrate is dried with nitrogen. It is then transferred to the vacuum chamber of a glove box where the moisture and oxygen contents are each less than 0.01 ppm to obtain the cleaned sapphire substrate.
[0088] (2) In a glove box where the moisture and oxygen contents are each less than 0.01 ppm, LaCl3, NH4Cl, KCl and LnCl3 were weighed separately and placed in a mortar. After grinding for 10 to 20 minutes, the mixture of LaCl3, NH4Cl, KCl and LnCl3 with a molar ratio of (5 to 40):(2 to 20):(2 to 16):1 was obtained.
[0089] Ln in LnCl3 is any one or a combination of at least two of Tb, Eu, or Ce;
[0090] (3) Place the cleaned sapphire substrate obtained in step (1) vertically at the bottom of the crucible and fix it, and then pour the mixture obtained in step (2) into the crucible;
[0091] The crucible was then placed in a muffle furnace and heated to 250°C–300°C at a heating rate of 10°C / min–30°C / min, and held for 40–80 min. Then, it was heated to 900°C–1100°C at a heating rate of 5°C / min–15°C / min, and held for 20–40 min. Finally, it was cooled to 600°C–800°C at a cooling rate of 1°C / min–10°C / min, and then cooled to 10°C–35°C at a cooling rate of 40°C / min–100°C / min, to obtain a sapphire substrate with LaOCl plate-like crystal material grown on its surface.
[0092] (4) The growth substrate with LaOCl plate-like crystal material on its surface is immersed in deionized water three times, each time for 3 min to 10 min, to obtain the cleaned growth substrate with LaOCl plate-like crystal material on its surface.
[0093] A PDMS stamp was inverted and placed on a growth substrate with LaOCl plate-like crystal material grown on its cleaned surface. Then, it was immersed in a mixture of ethanol and water with a volume ratio of (0.5-1.5):1 to obtain a PDMS stamp with nanosheets attached. Then, the PDMS stamp with LaOCl plate-like crystal material attached was attached to a single-sided polished silicon substrate with a crystal plane orientation of (100). The single-sided polished silicon substrate was then heated to 40℃-70℃ to cause the LaOCl plate-like crystal material to detach from the PDMS stamp, thereby transferring the LaOCl plate-like crystal material to the single-sided polished silicon substrate and obtaining the LaOCl plate-like crystal material.
[0094] In a second aspect, the present invention provides an application of the LaOCl sheet-like crystal material described in the first aspect, wherein the LaOCl sheet-like crystal material is used in photodetectors, semiconductor light-emitting devices, and micro-nano integrated devices.
[0095] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0096] Compared with the prior art, the present invention has the following beneficial effects:
[0097] The LaOCl plate-like crystal material provided by this invention has a domain size of not less than 100 μm, indicating that the wafers are grown and arranged in an orderly manner. Therefore, the LaOCl plate-like crystal material has good integration compatibility with micro-nano processing and has a wider range of applications.
[0098] The LaOCl sheet-like crystal material provided in this invention has an ordered arrangement structure, which can effectively improve the efficiency and convenience of nanosheet transfer and stacking processes, providing a reliable foundation for heterogeneous integration of materials and micro / nano devices, and further broadening the application scope of LaOCl sheet-like crystal materials in the field of micro / nano optoelectronic devices.
[0099] The LaOCl plate-like crystal material provided in this invention has fewer emission peaks and a smaller half-width at half-maximum of the main emission rare earth element peaks, thus exhibiting higher emission purity and further broadening the application range of the LaOCl plate-like crystal material. Attached Figure Description
[0100] Figure 1 This is a schematic diagram of the LaOCl sheet-like crystal material provided in Example 1 under a metallographic microscope.
[0101] Figure 2 This is a schematic diagram of the LaOCl sheet-like crystal material provided in Example 1 under a metallographic microscope.
[0102] Figure 3 This is a schematic diagram of the LaOCl sheet-like crystal material provided in Example 1 under a scanning electron microscope at a magnification of 1000x.
[0103] Figure 4 This is a schematic diagram of the LaOCl sheet crystal material provided in Example 1 under a scanning electron microscope at a magnification of 370x.
[0104] Figure 5 This is the elemental distribution diagram of the LaOCl plate-like crystal material provided in Example 1.
[0105] Figure 6 This is the EDS diagram of the LaOCl plate-like crystal material provided in Example 1.
[0106] Figure 7This is the Raman spectrum of the LaOCl plate-like crystal material provided in Example 1.
[0107] Figure 8 This is the elemental distribution diagram of the LaOCl plate-like crystal material provided in Example 2.
[0108] Figure 9 This is the EDS diagram of the LaOCl plate-like crystal material provided in Example 2.
[0109] Figure 10 This is the Raman spectrum of the LaOCl plate-like crystal material provided in Example 2.
[0110] Figure 11 These are comparison diagrams of the Raman spectra of the LaOCl plate-like crystal materials provided in Examples 1-2 and Comparative Example 1.
[0111] Figure 12 This is a transfer diagram of the LaOCl plate-like crystal material provided in Example 1.
[0112] Figure 13 The photoluminescence spectrum of the LaOCl plate-like crystal material provided in Example 1 is shown.
[0113] Figure 14 This is a transfer diagram of the LaOCl plate-like crystal material provided in Example 2.
[0114] Figure 15 The photoluminescence spectrum of the LaOCl plate-like crystal material provided in Example 2 is shown. Detailed Implementation
[0115] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0116] Example 1
[0117] This embodiment provides a LaOCl sheet-like crystal material doped with a luminescent rare earth element, wherein the luminescent rare earth element in the LaOCl sheet-like crystal material is Tb; based on the total molar amount of metal elements in the LaOCl sheet-like crystal material as 100%, the molar amount of the luminescent rare earth element accounts for 5.10%.
[0118] The wafers in the LaOCl sheet-like crystal material are rectangular wafers;
[0119] The preparation method includes:
[0120] (1) In an ultrasonic cleaner, acetone, ethanol, and deionized water are sequentially applied to the crystal orientation. <0001> After ultrasonic cleaning for 10 minutes, the sapphire substrate with a surface size of 10mm×10mm was removed, rinsed with deionized water, and then dried with nitrogen. It was then transferred to a vacuum chamber in a glove box with a moisture content of 0.005ppm and an oxygen content of 0.006ppm to obtain the cleaned sapphire substrate.
[0121] (2) In a glove box with a moisture content of 0.005 ppm and an oxygen content of 0.006 ppm, LaCl3, NH4Cl, KCl and TbCl3 were weighed separately and placed in a mortar. The mixture was then ground for 15 min to obtain a mixture with a molar ratio of 10:5:4:1.
[0122] (3) Place the cleaned sapphire substrate obtained in step (1) vertically at the bottom of the crucible and fix it, and then pour the mixture obtained in step (2) into the crucible;
[0123] The crucible was then placed in a muffle furnace and heated to 280°C at a heating rate of 20°C / min and held for 60 min. Then, it was heated to 1000°C at a heating rate of 10°C / min and held for 30 min. Finally, it was cooled to 700°C at a cooling rate of 5°C / min and then cooled to 25°C at a cooling rate of 50°C / min to obtain a sapphire substrate with LaOCl plate-like crystal material grown on its surface.
[0124] (4) The growth substrate with LaOCl plate-like crystal material on its surface was immersed in deionized water three times, each time for 5 minutes, to obtain the cleaned growth substrate with LaOCl plate-like crystal material on its surface.
[0125] A PDMS stamp was inverted and placed on a growth substrate with LaOCl flake crystals grown on its cleaned surface. Then, it was immersed in a mixture of ethanol and water with a volume ratio of 1:1 to obtain a PDMS stamp with nanosheets. Next, the PDMS stamp with LaOCl flake crystals was attached to a single-sided polished silicon substrate with a crystal orientation of (100). The single-sided polished silicon substrate was then heated to 55°C to remove the LaOCl flake crystals from the PDMS stamp, thus transferring the LaOCl flake crystals to the single-sided polished silicon substrate and obtaining the LaOCl flake crystals.
[0126] Example 2
[0127] This embodiment provides a LaOCl sheet-like crystal material doped with a luminescent rare earth element, wherein the luminescent rare earth element in the LaOCl sheet-like crystal material is Eu; based on the total molar amount of metal elements in the LaOCl sheet-like crystal material as 100%, the molar amount of the luminescent rare earth element accounts for 5.04%.
[0128] The wafers in the LaOCl sheet-like crystal material are rectangular wafers;
[0129] The preparation method includes:
[0130] (1) In an ultrasonic cleaner, acetone, ethanol, and deionized water are sequentially applied to the crystal orientation. <0001> After ultrasonic cleaning for 10 minutes, the sapphire substrate with a surface size of 10mm×10mm was removed, rinsed with deionized water, and then dried with nitrogen. It was then transferred to a vacuum chamber in a glove box with a moisture content of 0.003ppm and an oxygen content of 0.09ppm to obtain the cleaned sapphire substrate.
[0131] (2) In a glove box with a moisture content of 0.003 ppm and an oxygen content of 0.09 ppm, LaCl3, NH4Cl, KCl and EuCl3 were weighed separately and placed in a mortar. After grinding for 15 minutes, the mixture of LaCl3, NH4Cl, KCl and EuCl3 with a molar ratio of 10:5:4:1 was obtained.
[0132] (3) Place the cleaned sapphire substrate obtained in step (1) vertically at the bottom of the crucible and fix it, and then pour the mixture obtained in step (2) into the crucible;
[0133] The crucible was then placed in a muffle furnace and heated to 280°C at a heating rate of 20°C / min and held for 60 min. Then, it was heated to 1000°C at a heating rate of 10°C / min and held for 30 min. Finally, it was cooled to 700°C at a cooling rate of 5°C / min and then cooled to 10°C at a cooling rate of 50°C / min to obtain a sapphire substrate with LaOCl plate-like crystal material grown on its surface.
[0134] (4) The growth substrate with LaOCl plate-like crystal material on its surface was immersed in deionized water three times, each time for 5 minutes, to obtain the cleaned growth substrate with LaOCl plate-like crystal material on its surface.
[0135] A PDMS stamp was inverted and placed on a growth substrate with LaOCl flake crystals grown on its cleaned surface. Then, it was immersed in a mixture of ethanol and water with a volume ratio of 1:1 to obtain a PDMS stamp with nanosheets. Next, the PDMS stamp with LaOCl flake crystals was attached to a single-sided polished silicon substrate with a crystal orientation of (100). The single-sided polished silicon substrate was then heated to 55°C to remove the LaOCl flake crystals from the PDMS stamp, thus transferring the LaOCl flake crystals to the single-sided polished silicon substrate and obtaining the LaOCl flake crystals.
[0136] Example 3
[0137] This embodiment provides a LaOCl sheet-like crystal material doped with luminescent rare earth elements, wherein the luminescent rare earth elements in the LaOCl sheet-like crystal material include Tb; and the proportion of the luminescent rare earth elements in the total molar amount of metal elements in the LaOCl sheet-like crystal material is 1.00% based on the total molar amount of metal elements in the LaOCl sheet-like crystal material.
[0138] The wafers in the LaOCl sheet-like crystal material are rectangular wafers;
[0139] The preparation method includes:
[0140] (1) In an ultrasonic cleaner, acetone, ethanol, and deionized water are sequentially applied to the crystal orientation. <0001> After ultrasonic cleaning for 5 minutes, the sapphire substrate with a surface size of 10mm×10mm was removed, rinsed with deionized water, and then dried with nitrogen. It was then transferred to a vacuum chamber in a glove box with a moisture content of 0.005ppm and an oxygen content of 0.005ppm to obtain the cleaned sapphire substrate.
[0141] (2) In a glove box with a moisture content of 0.005 ppm and an oxygen content of 0.005 ppm, LaCl3, NH4Cl, KCl and TbCl3 were weighed separately and placed in a mortar. The mixture was then ground for 10 min to obtain a mixture with a molar ratio of 40:20:16:1.
[0142] (3) Place the cleaned sapphire substrate obtained in step (1) vertically at the bottom of the crucible and fix it, and then pour the mixture obtained in step (2) into the crucible;
[0143] The crucible was then placed in a muffle furnace and heated to 250°C at a heating rate of 10°C / min and held for 80 min. Then, it was heated to 1100°C at a heating rate of 15°C / min and held for 20 min. Finally, it was cooled to 600°C at a cooling rate of 10°C / min and then cooled to 25°C at a cooling rate of 40°C / min to obtain a sapphire substrate with LaOCl plate-like crystal material grown on its surface.
[0144] (4) The growth substrate with LaOCl plate-like crystal material on its surface was immersed in deionized water three times, each time for 10 minutes, to obtain the cleaned growth substrate with LaOCl plate-like crystal material on its surface.
[0145] A PDMS stamp was placed upside down on a growth substrate with LaOCl flake crystals grown on its cleaned surface. Then, it was immersed in a mixture of ethanol and water with a volume ratio of 0.5:1 to obtain a PDMS stamp with nanosheets. Then, the PDMS stamp with LaOCl flake crystals was attached to a single-sided polished silicon substrate with a crystal orientation of (100). The single-sided polished silicon substrate was then heated to 70°C to remove the LaOCl flake crystals from the PDMS stamp, thus transferring the LaOCl flake crystals to the single-sided polished silicon substrate and obtaining the LaOCl flake crystals.
[0146] Example 4
[0147] This embodiment provides a LaOCl sheet-like crystal material doped with luminescent rare earth elements, wherein the luminescent rare earth elements in the LaOCl sheet-like crystal material include Eu; and the proportion of the luminescent rare earth elements in the total molar amount of the metal elements in the LaOCl sheet-like crystal material is 1.00% based on the total molar amount of the metal elements in the LaOCl sheet-like crystal material.
[0148] The wafers in the LaOCl sheet-like crystal material are rectangular wafers;
[0149] The preparation method includes:
[0150] (1) In an ultrasonic cleaner, acetone, ethanol, and deionized water are sequentially applied to the crystal orientation. <0001> After ultrasonic cleaning for 15 minutes, the sapphire substrate with a surface size of 10mm×10mm was removed, rinsed with deionized water, and then dried with nitrogen. It was then transferred to a vacuum chamber in a glove box with a moisture content of 0.005ppm and an oxygen content of 0.005ppm to obtain the cleaned sapphire substrate.
[0151] (2) In a glove box with a moisture content of 0.005 ppm and an oxygen content of 0.005 ppm, LaCl3, NH4Cl, KCl and EuCl3 were weighed separately and placed in a mortar. After grinding for 20 minutes, the molar ratio of LaCl3, NH4Cl, KCl and EuCl3 was mixed to obtain a mixture.
[0152] (3) Place the cleaned sapphire substrate obtained in step (1) vertically at the bottom of the crucible and fix it, and then pour the mixture obtained in step (2) into the crucible;
[0153] The crucible was then placed in a muffle furnace and heated to 300°C at a heating rate of 30°C / min and held for 40 min. Then, it was heated to 900°C at a heating rate of 5°C / min and held for 40 min. Finally, it was cooled to 800°C at a cooling rate of 1°C / min and then cooled to 25°C at a cooling rate of 100°C / min to obtain a sapphire substrate with LaOCl plate-like crystal material grown on its surface.
[0154] (4) The growth substrate with LaOCl plate-like crystal material on its surface was immersed in deionized water three times, each time for 3 minutes, to obtain the cleaned growth substrate with LaOCl plate-like crystal material on its surface.
[0155] A PDMS stamp was inverted and placed on a growth substrate with LaOCl flake crystals grown on its cleaned surface. Then, it was immersed in a mixture of ethanol and water with a volume ratio of 1.5:1 to obtain a PDMS stamp with nanosheets. Then, the PDMS stamp with LaOCl flake crystals was attached to a single-sided polished silicon substrate with a crystal orientation of (100). The single-sided polished silicon substrate was then heated to 40°C to remove the LaOCl flake crystals from the PDMS stamp, thus transferring the LaOCl flake crystals to the single-sided polished silicon substrate and obtaining the LaOCl flake crystals.
[0156] Example 5
[0157] This embodiment provides a LaOCl sheet-like crystal material doped with luminescent rare earth elements, wherein the luminescent rare earth elements account for 0.5% of the total molar amount of metal elements in the LaOCl sheet-like crystal material, calculated as 100%.
[0158] That is, except for the mixture obtained by grinding and mixing LaCl3, NH4Cl, KCl and TbCl3 in a molar ratio of 60:30:24:1 in step (2) of the preparation method, the rest is the same as in Example 1.
[0159] Example 6
[0160] This embodiment provides a LaOCl sheet crystal material doped with luminescent rare earth elements, wherein the total molar amount of metal elements in the LaOCl sheet crystal material is 100%, and the molar amount of luminescent rare earth elements accounts for 8%.
[0161] That is, except for the mixture obtained by grinding and mixing LaCl3, NH4Cl, KCl and TbCl3 in a molar ratio of 5:2.5:2:1 in step (2) of the preparation method, all other steps are the same as in Example 1.
[0162] Example 7
[0163] This embodiment provides a LaOCl sheet-like crystal material doped with rare earth elements. Except for step (3) of the preparation method, in which the cleaned sapphire substrate obtained in step (1) is placed horizontally at the bottom of the crucible (i.e., the growth substrate is parallel to the bottom of the crucible) and fixed, and then the mixture obtained in step (2) is poured into the crucible, the rest is the same as in embodiment 1.
[0164] Example 8
[0165] This embodiment provides a luminescent rare-earth element-doped LaOCl sheet-like crystal material, except that the crystal orientation in step (1) of the preparation method is... <0001> Except for replacing the sapphire substrate with a surface size of 10mm×10mm with a silicon carbide substrate, everything else is the same as in Example 1.
[0166] Example 9
[0167] This embodiment provides a luminescent rare earth element-doped LaOCl sheet crystal material. Except for step (3) of the preparation method, which involves heating the material to 200°C at a heating rate of 20°C / min and holding it at that temperature for 60 min, and then heating it to 1000°C at a heating rate of 10°C / min and holding it at that temperature for 30 min, the rest of the process is the same as in Example 1.
[0168] Example 10
[0169] This embodiment provides a luminescent rare earth element-doped LaOCl sheet crystal material. Except for step (3) of the preparation method, which involves heating the material to 400°C at a heating rate of 20°C / min and holding it at that temperature for 60 min, and then heating it to 1000°C at a heating rate of 10°C / min and holding it at that temperature for 30 min, the rest of the process is the same as in Example 1.
[0170] Example 11
[0171] This embodiment provides a luminescent rare earth element-doped LaOCl sheet crystal material. Except for step (3) of the preparation method, which involves heating the material to 280°C at a heating rate of 20°C / min and holding it at that temperature for 60 min, and then heating it to 800°C at a heating rate of 10°C / min and holding it at that temperature for 30 min, the rest of the process is the same as in Example 1.
[0172] Example 12
[0173] This embodiment provides a luminescent rare earth element-doped LaOCl sheet crystal material. Except for step (3) of the preparation method, which involves heating the material to 280°C at a heating rate of 20°C / min and holding it at that temperature for 60 min, and then heating it to 1200°C at a heating rate of 10°C / min and holding it at that temperature for 30 min, the rest of the process is the same as in Example 1.
[0174] Comparative Example 1
[0175] This comparative example provides a LaOCl sheet-like crystal material, except that the luminescent rare earth element Tb doped in the LaOCl sheet-like crystal material is omitted;
[0176] The wafers in the LaOCl sheet-like crystal material are rectangular wafers;
[0177] Except for TbCl3 in step (2) of the preparation method, which is omitted, it is the same as in Example 1.
[0178] Comparative Example 2
[0179] This comparative example provides a LaOCl sheet-like crystal material, except that the luminescent rare earth element Eu doped in the LaOCl sheet-like crystal material is omitted;
[0180] The wafers in the LaOCl sheet-like crystal material are rectangular wafers;
[0181] Except for TbCl3 in step (2) of the preparation method, which is omitted, it is the same as in Example 2.
[0182] Metallographic and SEM tests were performed on the LaOCl plate-like crystal materials provided in the above embodiments and comparative examples. The domain sizes of the LaOCl plate-like crystal materials provided in the embodiments and comparative examples were obtained by observation using a metallographic microscope and SEM, as shown in Table 1. A schematic diagram of the LaOCl plate-like crystal material provided in Example 1 under a metallographic microscope is shown below. Figure 1 and Figure 2 As shown; a schematic diagram of the LaOCl sheet-like crystal material provided in Example 1 under a scanning electron microscope is shown. Figure 3 and Figure 4 As shown, by Figure 1It can be seen that the surface of the sheet-like crystal material provided in Example 1 is smooth and flat, and the crystal domain size reaches hundreds of micrometers.
[0183] EDS and Raman spectroscopy tests were performed on the LaOCl plate-like crystal materials provided in the above embodiments and comparative examples, respectively; the elemental distribution diagram of the LaOCl plate-like crystal material provided in Example 1 is shown below. Figure 5 As shown, the EDS plot is as follows Figure 6 As shown, the Raman spectrum is as follows Figure 7 As shown; the elemental distribution diagram of the LaOCl plate-like crystal material provided in Example 2 is as follows. Figure 8 As shown, the EDS plot is as follows Figure 9 As shown, the Raman spectrum is as follows Figure 10 As shown; a comparison diagram of the Raman spectra of the LaOCl plate-like crystal materials provided in Examples 1-2 and Comparative Example 1 is shown. Figure 11 As shown (wherein, the Raman spectrum of the LaOCl plate-like crystal material in Example 1 corresponds to...), Figure 11 The LaOCl:Eu curve in Example 2; the Raman spectrum of the LaOCl plate-like crystal material in Example 2, corresponding to... Figure 11 The curve of LaOCl:Tb in the figure; the Raman spectrum of the LaOCl plate-like crystal material in Comparative Example 1, corresponding to Figure 11 (The curve of LaOCl in the image); Analysis of the elemental distribution map and EDS diagram shows that the luminescent rare earth element was successfully incorporated into LaOCl; At the same time, the Raman spectrum shows that the Raman peaks of the LaOCl plate crystal materials provided in Examples 1 and 2 showed different degrees of peak shift and enhancement compared with the pure LaOCl material in Comparative Example 1, further indicating the successful doping of the luminescent rare earth element.
[0184] The lamellar crystal materials provided in the above embodiments and comparative examples were observed using a metallographic microscope, and the transfer pattern of the LaOCl lamellar crystal material provided in Example 1 was obtained as follows: Figure 12 As shown, the transfer diagram of the LaOCl plate-like crystal material provided in Example 2 is as follows. Figure 14 As shown in the figure; the transfer diagram is an effect diagram of transferring the doped LaOCl plate-like crystal material to a clean silicon wafer using a PDMS stamp. As can be seen from the transfer diagram, the luminescent rare earth element-doped LaOCl plate-like crystal material was successfully transferred to the clean silicon wafer surface, and the transferred LaOCl plate-like crystal material was relatively clean, effectively avoiding the influence of residual reaction materials on the sample PL test results.
[0185] The LaOCl plate-like crystal materials provided in the above embodiments and comparative examples were tested using a PL spectrometer to obtain the photoluminescence spectra of the LaOCl plate-like crystal materials provided in the embodiments and comparative examples. The number of emission peaks and the full width at half maximum (FWHM) of the main emission peaks of the rare earth elements in the LaOCl plate-like crystal materials are shown in Table 1. The photoluminescence spectrum of the LaOCl plate-like crystal material provided in Example 1 is as follows: Figure 13 As shown, the photoluminescence spectrum of the LaOCl plate-like crystal material provided in Example 2 is as follows: Figure 15 As shown; by Figure 13 and Figure 15 It can be seen that the LaOCl plate-like crystal materials provided in Examples 1 to 3 have obvious Tb-related properties in the visible light band of 380nm to 750nm. 3+ Eu 3+ The emission peak of the ions; wherein, in Example 1, it corresponds to Tb 3+ The emission peak is at 488 nm ( 5 D4→ 7 F6, main peak), 545nm ( 5 D4→ 7 F5) and 586nm 5 D4→ 7 F3), etc.; Eu in Example 2 3+ The emission peak is 617 nm ( 5 D0→ 7 F2 (main peak) and 700nm ( 5 D0→ 7 F1); at the same time, Figure 13 and Figure 15 The corresponding luminescent rare earth element Tb 3+ With Eu 3+ The full width at half maximum (FWHM) of the main peak is around 10 nm, indicating high luminescence purity. In summary, the doping of luminescent rare earth elements has broadened the application of LaOCl sheet-like crystal materials in the field of micro- and nano-sized light-emitting devices.
[0186] Table 1
[0187]
[0188]
[0189] From Table 1 and Figures 1-15 It can be known that:
[0190] (1) The LaOCl plate-like crystal materials doped with luminescent rare earth elements provided in Examples 1 to 4 have a crystal domain size of not less than 100 μm, a small number of luminescent peaks, and a narrow half-width of the main peak of the luminescent rare earth element, and have good comprehensive performance.
[0191] (2) A comparison of Examples 1 with Examples 5 and 6 shows that, taking the total molar amount of metal elements in the LaOCl plate-like crystal material as 100%, the molar amount of luminescent rare earth elements affects the performance of the LaOCl plate-like crystal material; when the molar amount of luminescent rare earth elements is 1% to 5%, the LaOCl plate-like crystal material has better performance. This is because: if the molar amount of luminescent rare earth elements (such as Tb) is 1%, the performance of the LaOCl plate-like crystal material is better. 3+ If the doping concentration is too low, the effective luminescence Tb per unit volume of the material will be low. 3+ The quantity will be significantly insufficient, and the LaOCl plate-like crystal material itself always has some intrinsic defects (such as vacancies, grain boundaries, etc.). Under photoexcitation conditions, the energy absorbed by the material is more easily captured by these defect energy levels, and then consumed through non-radiative transitions (thermal generation) or radiative transitions (generating a broad-spectrum, non-characteristic defect luminescence). The final luminescence spectrum is a superposition of weak rare earth ion characteristic peaks and strong broad-spectrum defect luminescence, which directly leads to an increase in the full width at half maximum (FWHM) and a significant decrease in color purity. However, a doping ratio of 1% to 5% can effectively balance the number of luminescent ions and the defect energy capture effect, thereby ensuring the material performance.
[0192] (3) By comparing Example 1 and Example 7, it can be seen that when the cleaned sapphire substrate is placed vertically at the bottom of the crucible (i.e. the growth substrate is perpendicular to the bottom of the crucible), the prepared LaOCl sheet crystal material has better performance. This is because when placed horizontally, the vapor generated by the thermal decomposition / sublimation of solid raw materials (LaCl3, NH4Cl, KCl, LnCl3) will preferentially accumulate in the area close to the substrate, forming a layer of high-concentration, uneven reactant vapor. This phenomenon will lead to poor lateral diffusion and exchange of vapor and by-products, which can easily cause local raw material depletion or by-product accumulation, affecting the continuous growth of crystals. However, by placing vertically, the reactant vapor can freely convection and diffusion in the crucible, thereby forming a gas phase environment with a gentler concentration gradient and more uniform distribution on the substrate surface. This change optimizes the gas phase transport process, temperature field and nucleation environment in the reaction chamber, thereby greatly promoting the ordered epitaxial growth of nanosheets.
[0193] (4) A comparison between Example 1 and Example 8 shows that, compared to other substrates, using a substrate with a crystal orientation of... <0001> Sapphire substrates are more conducive to improving the performance of the prepared LaOCl plate crystal materials. This is because lattice mismatch is a key factor in epitaxial growth. Large mismatch leads to high interface energy and generates a large number of defects (such as dislocations), which hinders the merging and growth of crystal nuclei and prevents the formation of large crystal domains. Compared with other substrates, sapphire's lattice parameters and symmetry can provide a relatively matched growth template for LaOCl, thereby inducing ordered epitaxial growth and ultimately obtaining large crystal domains of hundreds of micrometers, which is beneficial to improving the performance of LaOCl plate crystal materials.
[0194] (5) By comparing Example 1 with Examples 9 and 10, it can be seen that the temperature of the first heat treatment affects the performance of the LaOCl plate crystal material. When the temperature of the first heat treatment is 250℃~300℃, the LaOCl plate crystal material has better performance. This is because when the temperature is below 250℃, the moisture and impurities in the raw materials are not fully removed, resulting in an impure reaction environment in the subsequent high-temperature stage, chaotic nucleation, and the crystal nuclei cannot grow in an orderly manner. When the temperature of the first heat treatment is too high (400-550℃), the raw materials will react prematurely before the temperature reaches their melting point. This temperature is not enough to provide sufficient energy for nucleation, rotation, and splicing, thus consuming the reactants prematurely and ultimately limiting the expansion of the grains and uniform nucleation.
[0195] (6) By comparing Example 1 with Examples 11 and 12, it can be seen that the temperature of the second heat treatment affects the performance of the LaOCl plate crystal material. When the temperature of the second heat treatment is 900℃~1100℃, the LaOCl plate crystal material has better performance. This is because the second heat treatment is carried out at a higher temperature. The high temperature environment promotes the full diffusion of reactants and lattice recombination, promotes the formation of thermodynamically stable phase, effectively reduces impurity phases and defects, and significantly improves the phase purity and crystal quality of the LaOCl plate crystal material.
[0196] (7) By comparing Examples 1-2 with Comparative Examples 1-2, it can be seen that the domain size of the LaOCl plate crystal material provided by the present invention is not less than 100 μm, indicating that the wafers are grown and arranged in an orderly manner. Therefore, the LaOCl plate crystal material has good integration compatibility with micro-nano processing, and the LaOCl plate crystal material has a wider range of applications.
[0197] The LaOCl sheet-like crystal material provided in this invention has an ordered arrangement structure, which can effectively improve the efficiency and convenience of nanosheet transfer and stacking processes, providing a reliable foundation for heterogeneous integration of materials and micro / nano devices, and further broadening the application scope of LaOCl sheet-like crystal materials in the field of micro / nano optoelectronic devices.
[0198] The LaOCl plate-like crystal material provided in this invention has fewer emission peaks and a smaller half-width of the main emission rare earth element peak, thus exhibiting higher emission purity and further broadening the application range of the LaOCl plate-like crystal material.
[0199] In the preparation method provided by the present invention, by selecting anhydrous LaCl3, anhydrous NH4Cl, anhydrous KCl and anhydrous LnCl3 (Ln is one or a combination of two of Tb and Eu) as raw materials, and by adjusting the growth conditions of single crystal nanosheets on the growth substrate through heat treatment, the domain size of the LaOCl plate crystal material prepared by the preparation method can reach hundreds of micrometers, which is a significant improvement compared with the prior art.
[0200] In the preparation method provided by the present invention, the raw materials include KCl. KCl, as a flux, can repeatedly induce the directional splicing of LaOCl wafers, avoiding the problem of random stacking of wafers in traditional methods, and finally achieving the ordered growth and regular arrangement of nanosheets, thereby improving the structural uniformity of the prepared LaOCl sheet crystal material.
[0201] In the preparation method provided by the present invention, the obtained mixture is heat-treated on a growth substrate. The growth substrate provides a flat growth interface for the growth of LaOCl nanosheets. Combined with the synergistic effect of heat treatment and KCl flux, rectangular layered wafers are induced to be neatly arranged on the growth substrate.
[0202] In the preparation method provided by the present invention, the mixture obtained is heat-treated on the growth substrate, which not only promotes the formation of a thermodynamically stable phase, which is beneficial to defect repair, reduces non-radiative recombination centers, and improves luminescence efficiency, but also helps to improve the uniformity of luminescent rare earth element doping, thereby improving the luminescence purity of LaOCl plate crystal material.
[0203] The preparation method provided by this invention involves directly mixing solid raw materials such as LaCl3, NH4Cl, KCl and LnCl3 and then subjecting them to heat treatment. This eliminates the need for complex liquid phase treatment processes, removes solvent evaporation in the sol-gel method, high-pressure reaction conditions in the hydrothermal method, and multi-step filtration and washing steps in the coprecipitation method, greatly simplifies the operation process, significantly improves the convenience and operability of the process, and is suitable for large-scale production.
[0204] The preparation method provided by this invention directly mixes solid raw materials such as LaCl3, NH4Cl, KCl and LnCl3 and then performs heat treatment, eliminating the waste liquid treatment step that is inevitably generated in the liquid phase reaction, which is more environmentally friendly.
[0205] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the scope of protection and disclosure of the present invention.
Claims
1. A luminescent rare-earth element-doped LaOCl plate-like crystal material, characterized in that, The luminescent rare earth element in the LaOCl plate-like crystal material includes any one or a combination of at least two of Tb, Eu, or Ce. The domain size of the LaOCl plate-like crystal material is not less than 100 μm.
2. The LaOCl plate-like crystal material according to claim 1, characterized in that, Based on the total molar amount of metal elements in the LaOCl plate-like crystal material as 100%, the molar amount of luminescent rare earth elements accounts for 1% to 5.10%.
3. The LaOCl plate-like crystal material according to claim 1 or 2, characterized in that, The wafers in the LaOCl sheet-like crystal material are rectangular wafers.
4. A method for preparing the LaOCl plate-like crystal material according to any one of claims 1 to 3, characterized in that, The preparation method includes: A mixture of LaCl3, NH4Cl, KCl and LnCl3 was obtained, and the mixture was heat-treated on a growth substrate to obtain LaOCl plate-like crystal material. In the LnCl3, Ln is any one or a combination of at least two of Tb, Eu, or Ce.
5. The preparation method according to claim 4, characterized in that, The mixing method includes grinding, and the grinding time is 10 min to 20 min.
6. The preparation method according to claim 4, characterized in that, The molar ratio of LaCl3 to LnCl3 in the mixture is (5-40):1; Preferably, the molar ratio of NH4Cl to LnCl3 in the mixture is (2-20):1; Preferably, the molar ratio of KCl to LnCl3 in the mixture is (2-16):1; Preferably, the mixing and heat treatment process further includes: pouring the resulting mixture into a container containing a growth substrate; Preferably, the growth substrate is placed in a container, with the growth substrate placed perpendicular to the bottom of the crucible; Preferably, the growth substrate comprises a double-sided polished c-plane sapphire substrate; Preferably, the crystal orientation of the sapphire substrate is... <0001> .
7. The preparation method according to claim 4, characterized in that, The heat treatment includes a first heating, a first holding, a second heating and a second holding in sequence, and the resulting heat treatment yields a growth substrate with LaOCl plate-like crystal material grown on its surface. Preferably, the first heating rate is 10℃ / min to 30℃ / min, and the final temperature is the temperature of the first heat preservation. Preferably, the temperature of the first heat preservation is 250℃~300℃, and the time is 40min~80min; Preferably, the second heating rate is 5℃ / min to 15℃ / min, and the final temperature is the temperature of the second heat preservation. Preferably, the second heat preservation temperature is 900℃~1100℃, and the time is 20min~40min; Preferably, the heat treatment is followed by a first cooling and a second cooling in sequence; Preferably, the first cooling rate is 1℃ / min to 10℃ / min, and the final temperature is 600℃ to 800℃; Preferably, the second cooling rate is 40℃ / min to 100℃ / min, and the final temperature is 10℃ to 35℃.
8. The preparation method according to claim 4, characterized in that, The heat treatment process also includes sequentially cleaning and transferring the growth substrate on which LaOCl plate-like crystal material is grown.
9. The preparation method according to claim 4, characterized in that, The preparation method includes: (1) In an ultrasonic cleaner, acetone, ethanol, and deionized water are sequentially applied to the crystal orientation. <0001> After ultrasonic cleaning of the sapphire substrate for 5 to 15 minutes, the sapphire substrate is removed, rinsed with deionized water, and then the surface of the sapphire substrate is dried with nitrogen. It is then transferred to the vacuum chamber of a glove box where the moisture and oxygen contents are each less than 0.01 ppm to obtain the cleaned sapphire substrate. (2) In a glove box where the moisture and oxygen contents are each less than 0.01 ppm, LaCl3, NH4Cl, KCl and LnCl3 were weighed separately and placed in a mortar. After grinding for 10 to 20 minutes, the mixture of LaCl3, NH4Cl, KCl and LnCl3 with a molar ratio of (5 to 40):(2 to 20):(2 to 16):1 was obtained. Ln in LnCl3 is any one or a combination of at least two of Tb, Eu, or Ce; (3) Place the cleaned sapphire substrate obtained in step (1) vertically at the bottom of the crucible and fix it, and then pour the mixture obtained in step (2) into the crucible; The crucible was then placed in a muffle furnace and heated to 250°C–300°C at a heating rate of 10°C / min–30°C / min, and held for 40–80 min. Then, it was heated to 900°C–1100°C at a heating rate of 5°C / min–15°C / min, and held for 20–40 min. Finally, it was cooled to 600°C–800°C at a cooling rate of 1°C / min–10°C / min, and then cooled to 10°C–35°C at a cooling rate of 40°C / min–100°C / min, to obtain a sapphire substrate with LaOCl plate-like crystal material grown on its surface. (4) The growth substrate with LaOCl plate-like crystal material on its surface is immersed in deionized water three times, each time for 3 min to 10 min, to obtain the cleaned growth substrate with LaOCl plate-like crystal material on its surface. A PDMS stamp was inverted and placed on a growth substrate with LaOCl plate-like crystal material grown on its cleaned surface. Then, it was immersed in a mixture of ethanol and water with a volume ratio of (0.5-1.5):1 to obtain a PDMS stamp with nanosheets attached. Then, the PDMS stamp with LaOCl plate-like crystal material attached was attached to a single-sided polished silicon substrate with a crystal plane orientation of (100). The single-sided polished silicon substrate was then heated to 40℃-70℃ to cause the LaOCl plate-like crystal material to detach from the PDMS stamp, thereby transferring the LaOCl plate-like crystal material to the single-sided polished silicon substrate and obtaining the LaOCl plate-like crystal material.
10. An application of the LaOCl plate-like crystal material according to any one of claims 1 to 3, characterized in that, The LaOCl sheet-like crystal material is used in photoelectric detectors, semiconductor light-emitting devices, and micro / nano integrated devices.
Citation Information
Patent Citations
Preparation method of micro-nano structure LaOCl: Eu<3+> luminescent material
CN110358539A
PROCESS FOR PREPARATION OF LUMINOPHORE LaOCl DOPED WITH RARE EARTHS
RO132582B1